The effect of condensed tannins and dietary protein on ruminant intestinal nematode infections - Butter, Nicola L. (1999)
Endoparasitic control is still heavily reliant on the use of anthelmintic drugs, however, frequent use and mis-use of anthelmintics is leading to the development of multiple resistance. In the tropics and subtropics where marginal levels of nutrition lead to greater susceptibility to infection, animal death due to nematode infection remains widely apparent. Here, anthelmintics are either unaffordable, of inferior quality or extensive multiple resistance has made these drugs ineffective. Consequently, alternative methods of parasitic control are required that are practical and realistic for introduction into farm production systems. One such possibility could be the exploitation of forage species capable of reducing parasitic infection solely, or in conjunction, with limited drug use. In tropical and subtropical regions many plants contain condensed tannins due to stress induced by environmental conditions. Sheep fed forages containing condensed tannins have been reported to have reduced gastrointestinal nematode infections. The aim of the studies reported in this thesis was to determine whether the inclusion of a model condensed tannin, quebracho tannin, and/or the elevation of dietary protein could reduce the establishment and persistence of small intestinal nematode infections. Initial work using the Nippostrongylus brasiliensis-rat model demonstrated that the inclusion of 40 g quebracho tannin/kg in both high and low protein diets significantly (p<0.05) reduced the number of N. brasiliensis establishing in the small intestine. Mean total daily faecal egg counts were also significantly (p<0.05) reduced by dietary quebracho tannin, and high dietary protein concentration. Data obtained from using the Trichostrongylus colubriformis-sheep model demonstrated that faecal egg counts were significantly (p<0.05) reduced when 50 g quebracho tannin/kg was included in a low protein diet. Increasing the dietary protein concentrations also reduced faecal egg counts to similar levels. The inclusion of quebracho tannin in a high protein diet did not significantly (p>0.2) reduce total daily faecal egg counts. Haematological and serological parameters did not show any significant (p>0.2) differences between dietary treatments. Subsequent investigations showed that dietary quebracho tannin was not reducing worm establishment and persistence by elevating the host immune response. Further studies suggested that quebracho tannin was acting through a direct toxic effect against the worm, where the mucosal inhabiting nematode, Trichinella spiralis, was unaffected by the presence of dietary quebracho tannin and in vitro data where N. brasiliensis survival was compromised by incubating worms in quebracho tannin-containing media. Concentrations as low as 0.01% (w/v) quebracho tannin proved effective at accelerating worm death. Thus, dietary quebracho tannin may be an alternative to increasing dietary protein concentration, which increases the hosts' capacity to mount an immune response and expel the worm burden from the small intestine. These data suggest that feeding condensed tannins may be a suitable alternative to anthelmintics, especially in the areas of the tropics and subtropics. However, the potential anthelmintic dietary properties of condensed tannins may be limited to parasites that are in direct contact with digesta and/or feed on intestinal contents, mucus and mucosal cells. Similarly, the diverse nature of condensed tannins may result with anthelmintic properties being restricted to a specific condensed tannin structure.